Realist review of community coalitions and outreach interventions to increase access to primary care for vulnerable populations: a realist review - Vivian Welch; Kevin Pottie; Caroline Gaudet; Micere Thuku; Ryan Mallard; Shannon Spenceley; Nida Amjed; Arpana Wadhwani; Elizabeth Ghogomu; Cathie Scott; Simone Dahrouge; The IMPACT Team (BMC, 2023)
Abstract Background There are meaningful gaps in equitable access to Primary Health Care (PHC), especially for vulnerable populations after widespread reforms in Western countries. The Innovative Models Promoting Access-to-Care Transformation (IMPACT) research program is a Canadian-Australian collaboration that aims to improve access to PHC for vulnerable populations. Relationships were developed with stakeholders in six regions across Canada and Australia where access-related needs could be identified. The most promising interventions would be implemented and tested to address the needs identified. This realist review was conducted to understand how community coalition and outreach (e.g., mobile or pop-up) services improve access for underserved vulnerable residents. Objective To inform the development and delivery of an innovative intervention to increase access to PHC for vulnerable populations. Methods A realist review was conducted in collaboration with the Local Innovative Partnership (LIP) research team and the IMPACT research members who conducted the review. We performed an initial comprehensive systematic search using MEDLINE, EMBASE, PsycINFO, and the Cochrane Library up to October 19, 2015, and updated it on August 8, 2020. Studies were included if they focused on interventions to improve access to PHC using community coalition, outreach services or mobile delivery methods. We included Randomized Controlled Trials (RCTs), and systematic reviews. Studies were screened by two independent reviewers and the Reach, Effectiveness, Adoption, Implementation, and Maintenance (RE-AIM) framework was used for data extraction and framework analysis to obtain themes. The LIP research team was also allowed to suggest additional papers not included at screening. Results We included 43 records, comprising 31 RCTs, 11 systematic reviews, and 1 case control study that was added by the LIP research team. We identified three main themes of PHC interventions to promote access for vulnerable residents, including: 1) tailoring of materials and services decreases barriers to primary health care, 2) services offered where vulnerable populations gather increases the "reach" of the interventions, 3) partnerships and collaborations lead to positive health outcomes. In addition, implementation designs and reporting elements should be considered. Conclusion Realist reviews can help guide the development of locally adapted primary health care interventions.